The Sequential Development of Antiglomerular Basement Membrane Nephritis and Myeloperoxidase-antineutrophil Cytoplasmic Antibody-associated Vasculitis - Ohashi, Naro (Intern Med, 2017)
A 55-year-old woman presented with deafness, increased levels of myeloperoxidase (MPO)-antineutrophil cytoplasmic antibody (ANCA), and renal insufficiency with proteinuria and hematuria. Renal biopsy revealed crescentic glomerulonephritis with the linear deposition of immunoglobulin G along the glomerular basement membrane (GBM) and peritubular capillaritis. The anti-GBM antibody levels on admission and 10 days after admission were 11.7 U/mL and 127 U/mL, respectively. These results indicated the sequential development of anti-GBM nephritis and MPO-ANCA-associated vasculitis. This report shows that anti-GBM nephritis may be caused by MPO-ANCA-associated vasculitis because of preceding otitis media, the sequential anti-GBM antibody titers, and the findings of peritubular capillaritis.